Les préférences tarifaires canadiennes et la libéralisation des échanges - Ahmad, Jaleel (L'Actualité économique, 1976)
AbstractThe developing countries currently enjoy preferential entry on designated exports of manufactures under the Canadian Scheme of Generalized Preferences introduced in 1974. This paper makes a quantitative assessment of the erosion of such preferential margins likely to result from current multilateral tariff negotiations at GATT. Estimates are made under four alternative tariff-cutting techniques.